4-Chloromercuribenzoic acid enhances carbapenem sensitivity among pathogenic Gram negative bacteria by altering blaVIM, adeB and ompC expression - Arijit Pal; Anusri Tripathi (Elsevier, 2020)
Background: Rapid global dissemination of carbapenem resistant Gram negative bacteria (CRGNB) is supposed to be clinically most alarming. Since, p-chloromercuribenzoic acid (pCMB) is a well known metallo-beta-lactamase inhibitor; evaluation of its bactericidal and carbapenem resistance reversing potential would be important. Methods: In this study, bactericidal and meropenem resistance reversing potential of pCMB was investigated against CRGNB by MIC determination, checkerboard assay, time-kill assay and cellular viability assay. Effect of pCMB on cellular morphology was visualized by Scanning Electron Microscopy. Further, quantitative Real Time-PCR was performed to evaluate effects of pCMB on clinically relevant metallo-beta-lactamases, major efflux pumps and outer membrane proteins expression. Results: pCMB exhibited at least four fold reduced MIC value (2-256 μg/ml) than that of meropenem against CRGNB. Moreover, pCMB exhibited synergism with meropenem against 86.06% of CRGNB. MIC of pCMB (16−32 μg/ml) could kill upto 99.96% bacteria within 6−8 h of dosing. pCMB exerted bactericidal activity by severely disrupting cell wall integrity. Reversal of carbapenemase property of CRGNB by pCMB might have developed through alteration of blaVIM, acrB, mexB and ompk36 expression. Conclusions: Hence, the current study identified pCMB as a potential bactericidal agent which enhanced meropenem sensitivity by altering blaVIM, acrB, mexB and ompk36 expression. Keywords: 4-Chloromercuribenzoic acid (pCMB), Bactericidal, Meropenem potentiation, Quantitative Real Time-PCR, Scanning Electron Microscope